# Find the remainder when f(x) is divided by (x - k)

f(x) = 5x^{4} + 8x^{3} + 4x^{2} - 5x + 67; k = 2

**Solution:**

Given a polynomial f(x) = 5x^{4} + 8x^{3} + 4x^{2} - 5x + 67. The divisor (x - k) is also a linear polynomial.

Thus we apply the remainder theorem to find the remainder

When f(x) is divided by (x-a), then the remainder is f(a).

Thus here f(x) = 5x^{4} + 8x^{3} + 4x^{2} - 5x + 67 is divided by (x - k)

⇒ x = k where value of k = 2 (given)

f(k = 3) = 5(2)^{4} + 8(2)^{3} + 4(2)^{2} - 5(2) + 67

f(k) = 80 + 64 + 16 - 10 + 67

f(k) = 217

## Find the remainder when f(x) is divided by (x - k)

f(x) = 5x^{4} + 8x^{3} + 4x^{2} - 5x + 67; k = 2

**Summary:**

Therefore, the remainder when f(x) = 5x^{4} + 8x^{3} + 4x^{2} - 5x + 67 is divided by (x - k); k = 2 is 217.

Math worksheets and

visual curriculum

visual curriculum